2021
DOI: 10.1371/journal.ppat.1009878
|View full text |Cite
|
Sign up to set email alerts
|

Differential plasmacytoid dendritic cell phenotype and type I Interferon response in asymptomatic and severe COVID-19 infection

Abstract: SARS-CoV-2 fine-tunes the interferon (IFN)-induced antiviral responses, which play a key role in preventing coronavirus disease 2019 (COVID-19) progression. Indeed, critically ill patients show an impaired type I IFN response accompanied by elevated inflammatory cytokine and chemokine levels, responsible for cell and tissue damage and associated multi-organ failure. Here, the early interaction between SARS-CoV-2 and immune cells was investigated by interrogating an in vitro human peripheral blood mononuclear c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 66 publications
7
59
0
Order By: Relevance
“…4) Interferon is one of the regulators of ACE2 receptor ( 22 ). Additionally, host IFN-I possesses high sensitivity to both SARS-CoV-2 virus and ACE2 receptors, especially in COVID-19 patients with asymptomatic manifestation ( 23 ), suggesting that understanding the genetic signature of IFN-I-associated genes in SARS-CoV-2 infection may serve as indicators of COVID-19 diagnosis. 5) Recent reports suggested that detection of IFN-I gene expression may be of great significance to measure the severity of COVID-19 ( 21 ), indicating that varied IFN-I-related gene profile may stratify the severity of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…4) Interferon is one of the regulators of ACE2 receptor ( 22 ). Additionally, host IFN-I possesses high sensitivity to both SARS-CoV-2 virus and ACE2 receptors, especially in COVID-19 patients with asymptomatic manifestation ( 23 ), suggesting that understanding the genetic signature of IFN-I-associated genes in SARS-CoV-2 infection may serve as indicators of COVID-19 diagnosis. 5) Recent reports suggested that detection of IFN-I gene expression may be of great significance to measure the severity of COVID-19 ( 21 ), indicating that varied IFN-I-related gene profile may stratify the severity of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the TLR7 response is critical for favorable outcome of COVID-19 [56,57], highlighting the clinical importance of the innate immune system in SARS-CoV-2 infection. However, in an in vitro study, it has been shown that SARS-CoV-2 induces a TLR7/8-dependent type I and III IFN response in peripheral blood mononuclear cells, which could be protective or may contribute to the cytokine storm observed in COVID-19 [58] and requires future investigation. Although there is a need for further investigation in this regard, IFN-α2b treatment has been shown to reduce viral replication, as well as IL-6 and CRP levels [59].…”
Section: Tlr Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…During influenza infection, pDCs are a major source of type I IFNs, causing the expansion of antigen-specific T cells ( 415 418 ). pDC-derived type I IFNs also inhibit viral replication in airway epithelial cells following SARS-CoV-2 infection ( 419 421 ). They play a nonredundant role in host defense against Aspergillus infection.…”
Section: Copathogenesis Of Respiratory Viral-fungal Coinfectionsmentioning
confidence: 99%
“…More recently, it was shown that recruitment of pDCs into the lungs activates neutrophil NADPH activity to promote clearance of inhaled conidia ( 316 ). Importantly, severe COVID-19 patients show gene expression signatures of apoptosis in pDCs that correlate with reduced pDC frequency ( 278 , 405 , 419 , 421 ). Dysregulation of pDCs might contribute to depressed IFN signatures affecting susceptibility to fungal coinfections.…”
Section: Copathogenesis Of Respiratory Viral-fungal Coinfectionsmentioning
confidence: 99%